Proximal interruption of the pulmonary artery: A review of radiological findings - Zhang, Ming-Jie; Cao, Ya-Xian; Zhou, Ning; Wang, Rui; Wu, Hui-Ying; Zhang, Xiao-Chun (Frontiers in Pediatrics, 2022)
Objectives Proximal interruption of the pulmonary artery (PIPA) has various clinical manifestations. This review focused on and summarized the clinical and radiological features of PIPA, based on relevant literature studies. Methods The study included a total of 25 PIPA cases in the Guangzhou Women and Children's Medical Center between January 2015 and December 2021. Conventional chest photographs and chest computed tomography angiography (CCTA) of patients with PIPA were analyzed and summarized. Results The radiological results showed that 17 cases were right-sided and 8 cases were left-sided PIPA. Additionally, the percentage of pulmonary hypoplasia on the affected side was 44%, 36% for pulmonary hypertension, 28% for the mosaic sign, 20% for subpleural cystic lucency shadow, 20% for subpleural serrated shadow, 20% for collateral vessel thickening, 16% for subpleural band-like parenchyma, 12% for pneumonia, and 56% for patent ductus arteriosus. Conclusion The clinical manifestations of PIPA are non-specific. Awareness of this anomaly, based on radiological manifestations, particularly those observed on CCTA images, is important for ruling out alternative diagnoses and implementing appropriate management.